Synopsis, Cereal productivity and its drivers: The case of Ethiopia - Bachewe, Fantu Nisrane; Koru, Bethlehem; Taffesse, Alemayehu Seyoum (Ethiopian Development Research Institute, 2015)
Cereal production has exhibited unprecedented growth in Ethiopia, leading to important welfare improvements in the country. However, it is not well understood what the drivers have been of this growth and how it can be sustained. In particular, there is a lack of evidence on the contribution of improvements in productivity to growth in yields. Moreover, doubts exist on whether it is possible to sustain such growth on declining landholdings. We study cereal production using a unique large-scale survey of households and analyze productivity is-sues using stochastic frontier and data envelopment analyses, two conceptually dissimilar methods. Production frontier estimates indicate that modern inputs contribute significantly to improvements in yields. The two analytical methods used indicate that an average cereal producing household is less than half as efficient as optimally producing households, and, consequently, there is considerable opportunity for additional growth in cereal production in Ethiopia.